Meningkatkan Aktivitas dan Hasil Belajar Matematika Menggunakan Model PRIMER di Kelas V Sekolah Dasar - Rahmawati; Herti Prastitasari (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The problem in this study is the lack of activity and low learning outcomes of students' mathematics. To overcome this problem, efforts are made to use the PRIMER model in learning. This study aims to describe teacher activity, analyze the increase in student activity and learning outcomes. This study used a qualitative approach with the type of classroom action research which was carried out in four meetings in the VB class of SDN Mawar 2 Banjarmasin. The type of data used is qualitative and quantitative data. The results of this study indicate that teacher activity has increased at meeting 1 obtaining a score of 29 until meeting 4 obtaining a score of 38. Student activity has increased, at meeting 1 reaching 59.26% up to meeting 4 reaching 96.30%. Learning outcomes experienced an increase in the cognitive aspects of meetings 1 to 4 increasing from 59.26% to 92.59%, affective at meetings 1 to 4 increasing from 74.07% to 92.59% and psychomotor at meetings 1 to 4 increasing from 59.26% to 92.59%. It was concluded that the PRIMER model was able to increase the activity and learning outcomes of students. The results of this study are expected to be used as a contribution to innovation or alternative learning models.